The crabs of Todos Santos Bay, Baja California. Part II. Grapsidae, Pinnotheridae and Ocypodidae (Crustacea: Decapoda: Brachyura) - R Bonfil; A Carvacho; E Campos (Ciencias Marinas, 1992)
In this, the second work of the series, we have included the families Grapsidae (three species in the bay), Pinnotheridae (seven species) and Ocypodidae (one species). Bioecological data based on monthly field observations are presented together with a revision of the literature for each species. An identification key (Appendix 1) is provided as well as an original figure for each species. The field work was based on monthly collections from the supralittoral to 25 m depth at 31 stations during a one year campaign. The collections were made by hand, SCUBA diving and using a beam trawl.